Endobronchial ultrasound with a guide sheath for small malignant pulmonary nodules: a retrospective comparison between central and peripheral locations - Chavez, Christine; Sasada, Shinji; Izumo, Takehiro; Watanabe, Junko; Katsurada, Masahiro; Matsumoto, Yuji; Tsuchida, Takaaki (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Objectives: Radial endobronchial ultrasound with a guide sheath (EBUS-GS) has improved the diagnostic accuracy of transbronchial biopsy (TBB) for malignant peripheral pulmonary nodules (PPNs). Many underscore the importance of tumor localization but reproducible results on other aspects that affect yield are few. We aimed to analyze the diagnostic performance of TBB with EBUS-GS and to know what group of patients can benefit most. Methods: The database of patients with malignant PPNs (≤30 mm) who underwent EBUS-GS TBB at the National Cancer Center Hospital, Tokyo, Japan from April 2012 to March 2013 was retrospectively reviewed and analysed based on lesion and procedural characteristics. Results: Most PPNs (N=212) were adenocarcinoma, measuring 20 mm [mean, standard deviation (SD) 5.45]. Overall diagnostic accuracy was 67.5% (143 of 212 cases). Factors that significantly affected and predicted diagnostic success were EBUS probe within (P=0.001) and parenchymal location that was not adjacent to the costal visceral pleura (P=0.001). When combined, these variables achieved an 87% (59 of 68 lesions) diagnostic yield. CT scan characteristic, lesion size, lobe location, and GS size were non-contributory. Conclusions: EBUS-GS TBB is an acceptable diagnostic method for small peripheral lung cancer. It can be maximized for PPNs that are away from the pleura and when the EBUS probe can be placed within the lesion.